(untitled) (Research, Society and Development, 2021)
The present work aimed of studying the influence of recombinant bovine somatotropin (rbST) on quantity and quality of in vivo aspirated oocytes, embryo production and gene expression of insulin-like growth factors (IGFs) types I and II in in vitro produced embryos from bovine females of Nelore breed. Five cows were treated with two administrations of 2mL of saline solution as placebo, with an interval of 14 days between them, being the first administration held 19 and the second 5 days before follicular aspirations; within 30 days after these aspirations, in a crossover design, the same protocol was used in these five animals being, in this case, the saline solution replaced by 500mg of rbST in order to perform comparisons between treatments. From retrieved oocytes, in vitro production (IVP) was performed, being all stages involving this process evaluated with subsequent achievement of polymerase chain reactions in real time (qPCRs) for gene expression of IGF-I and IGF-II in produced blastocysts. It was observed that the rbST, although having a numerical increase, did not show significant influence, on the parameters studied, on the quantity and quality of in vivo aspirated oocytes, embryo production and gene expression of IGF-I and IGF-II in in vitro produced embryos from bovine females of Nelore breed.